Online customer satisfaction about sharing bike market in China - Chen Li (2022)
Sharing bike, which makes the replacement of private car travel possible, solved the “last mile” problem and changed people’s travel idea from individual ownership to sharing service. It is an environmentally friendly way of travel, which is quite popular in China. Users' satisfaction with sharing bicycles is essential in determining whether users continue to use these bicycles. The Internet is an important place for users to evaluate sharing bicycles. It is significant for developing public transportation in China to study sharing bike satisfaction by collecting online public opinion data. This paper takes the satisfaction of sharing bicycles in China as the research object, collects the public opinion information about sharing bicycles on the Internet, and obtains the satisfaction data of sharing bicycles by using text mining. In addition, the descriptive statistical analysis and comparative study were carried out on four major brands in China (Didi, Meituan, Hello, and Ofo). It is found that Didi's satisfaction with sharing bicycles is the highest, and Ofo is the lowest. The price increase of sharing bicycles does not affect its satisfaction in most cases, and only a few cases will reduce the satisfaction. This paper also studies the correlation between weather and sharing bicycles satisfaction using descriptive statistics, correlation analysis and factor analysis. Chengdu and Beijing were the two cities that selected to analyze the correlation between the weather conditions and sharing bikes satisfaction. In the research on the satisfaction of sharing bicycles in Beijing, it is found that there is a specific correlation between weather conditions, air temperature, and air pressure and the satisfaction. The satisfaction on sunny days is higher than that on cloudy days. In the research on the satisfaction of shared bicycles in Chengdu, it is found that the weather conditions do not affect user satisfaction of sharing bikes, and the public opinions, maximum temperature, and wind speed are related to the satisfaction.